Parameters for Ramanujan’s function $χ(q)$ of degree five and their explicit evaluation - Dharmendra, B. N. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We study the ratios of parameters for Ramanujan’s function $χ(q)$ and their explicit values.